2009
DOI: 10.1016/j.neuroimage.2008.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of MRI-derived cortical and subcortical morphometric measures: Effects of pulse sequence, voxel geometry, and parallel imaging

Abstract: Advances in magnetic resonance imaging (MRI) have contributed greatly to the study of neurodegenerative processes, psychiatric disorders, and normal human development, but the effect of such improvements on the reliability of downstream morphometric measures has not been extensively studied. We examined how MRI-derived neurostructural measures are affected by three technological advancements: parallel acceleration, increased spatial resolution, and the use of a high bandwidth multiecho sequence. Test-retest da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
182
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(198 citation statements)
references
References 24 publications
15
182
1
Order By: Relevance
“…SBM is a recently-developed and highly reliable MRI-derived neuroanatomical measure, which overcomes the shortcomings of volume-based analysis, and is unaffected by voxel geometry [42]. In this study, we found thinning of the bilateral occipital lobe, lingual gyrus, cuneus, and lunate cortex in amblyopia.…”
Section: Discussionmentioning
confidence: 48%
“…SBM is a recently-developed and highly reliable MRI-derived neuroanatomical measure, which overcomes the shortcomings of volume-based analysis, and is unaffected by voxel geometry [42]. In this study, we found thinning of the bilateral occipital lobe, lingual gyrus, cuneus, and lunate cortex in amblyopia.…”
Section: Discussionmentioning
confidence: 48%
“…It is well documented that using parallel imaging has the effect of creating variable spatial signal-to-noise ratio (SNR), being particularly worse in the center of the image (14). However, Wonderlick et al (15) discussed that, with conservative parallel imaging factors, there is a ''negligible effect on reliability of morphometric measures'' when examining the MPRAGE sequence. In addition, with respect to SNR, it should be noted that the use of highly sensitive coils, such as the 32-channel coil employed in the Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been demonstrated to show good test-retest reliability across scanner manufacturers and across field strengths (Han et al, 2006;Wonderlick et al, 2009;Reuter et al, 2012), although other studies have shown discrepancies in test-retest reliability (Morey et al, 2010;Gronenschild et al, 2012). It should be noted that the task of automated cortical labelling is extremely challenging.…”
Section: Sources Of Test-retest Variationmentioning
confidence: 99%